Effect of binder to fine aggregate content on performance of sustainable alkali activated mortars incorporating solid waste materials - Huseien, G.; Ismail, Mohamed; Tahir, M.; Mirza, J.; Hussein, A.; Khalid, N.; Sarbini, N. (The Italian Association of Chemical Engineering, 2018)
This article investigated the effects of binder to aggregate ratio on the properties of granulated blast furnace slag (GBFS) alkali activated mortar incorporated with fly ash (FA), waste ceramic (CP) and bottle glass wastes (GP). Five types of alkali-activated mortars were prepared with a different binder to fine aggregate ratio (B:A) 0.30, 1.0, 1.5, 2.0 and 2.5. Sodium hydroxide (NH) with 6 molar concentrations added to sodium silicate (NS) and used as alkali activator solution, alkaline liquid to binder ratio (S:B) was kept 0.25 for all mixtures. Alkali-activated samples cured at ambient temperature (27 °C) and relative humidity (75 %). The results indicated that 1.0 (B:A) ratio was achieved the optimum results flow and bending stress, increasing binder to fine aggregate content effect negatively on workability and strength properties of alkali-activated mortars. The results also presented the porosity of alkali-activated samples has been influenced by increase binder content to fine aggregate from 1.0 to 2.5.